Effects of shoes on children`s fundamental motor skills performance - Khajooei, M.; Wochatz, M.; Baritello, O.; Mayer, F. (Footwear Science, 2020)
Progression or impediment of fundamental motor skills performance (FMSP) in children depends on internal and environmental factors. Shoes as an environmental constraint are believed to affect these movements as children showed to perform qualitatively better with sports shoes than flip-flop sandals. However, locomotor performance assessments based on biomechanical variables are limited. Therefore, the objective of this experiment was to assess the biomechanical effects of wearing shoes while performing fundamental motor skills in children. Barefoot and shod conditions were tested in healthy children between the age of 4 and 7 years. They were asked to perform basic and advanced motor skills including double-leg stance, horizontal jumps, walking as well as counter-movement jumps, single-leg stance and sprinting. Postural control and ground reaction data were measured with two embedded force plates. A 3D motion capture system was used to analyse the spatiotemporal parameters of walking and sprinting. Findings showed that the parameters of single- and double-leg stance, horizontal and counter-movement jump did not differ between barefoot and shod conditions. Most of the spatiotemporal variables including cadence, stride length, stride time, and contact time of walking and sprinting were statistically different between the barefoot and shod conditions. Consequently, tested shoes did not change performance and biomechanics of postural control and jumping tasks; however, the spatiotemporal gait parameters indicate changes in walking and sprinting characteristics with shoes in children.